UMKM DAN PERTUMBUHAN EKONOMI DI INDONESIA - Fitri Salekhah (EKSYDA: Jurnal Studi Ekonomi Syariah, 2022)
Abstract (English) The purpose of this research is to analyse the influence of MSMEs‟ stability toward Indonesia‟s economic growth. This research picks the number of MSME units, Number of MSME workers, and the export value of it as the independent variables. The method in this study uses multiple regression analysis. The results showed the number of MSME units and MSME workers did not significantly affect economic growth in Indonesia, while the export value of MSMEs showed a significant effect toward Indonesia‟s economic growth.